Composite negative electrode and preparation method and application thereof
By constructing a cocoon-structured carbon material on the surface of the lithium-containing particles of the lithium-ion battery anode material, the problem of volume expansion and dendrite growth of the lithium-ion battery anode material during cycling is solved, and the cycle performance and rate performance of the battery are improved.
Patent Information
- Application Number
- CN202310893749.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-20
- Publication Date
- 2025-01-21
AI Technical Summary
The existing lithium-ion battery negative electrode materials have volume expansion and dendrite growth problems during the circulation process, resulting in a decline in battery performance, and the prelithiation method cannot effectively improve the negative electrode capacity.
By constructing structural carbon materials for lithium particles such as lithium powder and/or lithium alloy powder, a stable porous skeleton is formed, the utilization rate of lithium -containing particles is improved, and the volume expansion problem is relieved.
Effectively improve the cycle performance and magnification performance of composite negative electrodes, take into account the capacity, cycle performance and multiplier performance, and reduce the amount of conductive agent and adhesive.
Smart Images

Figure CN119340342A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of new materials, and in particular relates to a composite negative electrode and a preparation method and application thereof. Background Art
[0002] As one of the mainstream commercial batteries, lithium-ion batteries are widely used in electronic devices, new energy vehicles, energy storage power stations and other fields. The negative electrode is an important component of lithium-ion batteries. The existing negative electrode materials include graphite, silicon carbon and silicon oxygen. This type of negative electrode material has common problems, such as low initial coulomb efficiency. This is because the SEI generation on the negative electrode surface consumes a large amount of lithium, causing the actual specific energy of the battery to drop significantly.
[0003] In recent years, researchers have proposed a pre-lithiation strategy to improve the first coulombic efficiency of negative electrode materials. Commonly used pre-lithiation agents include metal lithium foil and metal lithium powder. Among them, CN 114765254A discloses a method for pre-lithiation of negative electrode sheets, which uses a dry process to mix metal lithium powder into the electrode sheet to compensate for the lithium consumed by the negative electrode due to the formation of SEI during the first charging of the battery, thereby effectively improving the battery energy density. However, after the metal lithium powder is treated with inertness, the generated passivation layer has poor conductivity, which reduces the utilization rate of the metal lithium powder; after the metal lithium powder takes effect, holes or cavities will be formed on the negative electrode, the current density is uneven, and lithium dendrites are easily generated during the cycle. In addition, pre-lithiation can only solve the problem of low first coulombic efficiency, but cannot improve the capacity of the negative electrode.
[0004] CN102201565A discloses a high-capacity metal lithium powder composite negative electrode and a preparation method and a multilayer composite electrode. The high-capacity negative electrode is prepared by mixing metal lithium powder, a binder such as PVDF, and a negative electrode material such as graphite. The metal lithium powder reacts with PVDF, causing the bonding performance of PVDF to decrease or even fail, while part of the metal lithium is lost; and the problem of volume expansion and dendrite growth of metal lithium during the cycle cannot be solved.
[0005] Based on this, how to develop a high-capacity composite negative electrode that can fully utilize metallic lithium powder and solve the volume expansion problem and dendrite growth problem of metallic lithium during the cycle of the composite negative electrode, while taking into account specific capacity, cycle performance and rate performance, has become an urgent problem to be solved. Summary of the invention
[0006] The present invention aims to effectively solve the above technical problems. The inventors found that by constructing structural carbon materials on the surface of lithium-containing particles such as metal lithium powder and / or lithium alloy powder to form a cocoon structure, the structural carbon materials are cross-entangled with each other to form a stable porous skeleton, which can effectively solve the problems of metal lithium volume expansion and lithium dendrite growth during the cycle, while improving the utilization rate of lithium-containing particles.
[0007] In a first aspect, the present invention provides a composite negative electrode, comprising a current collector and a negative electrode active material layer arranged on at least one side of the current collector, wherein the weight proportion of the negative electrode active material layer is as follows: 40-78 parts of negative electrode material; 20-50 parts of cocoon structure lithium-carbon material; 1-5 parts of conductive agent; 1-5 parts of binder, and the sum of the weight proportions of all components is 100 parts by weight; wherein the cocoon structure lithium-carbon material comprises a cocoon body formed by a structural carbon material and one or more lithium-containing particles contained in the cocoon body.
[0008] In the present invention, the structural carbon material forms a cocoon on the lithium-containing particles to construct a continuous and stable three-dimensional electronic network channel, has good conductivity, and improves the utilization rate of the lithium-containing particles in the composite negative electrode; the cocoon acts on the lithium-containing particles in a limited domain, effectively alleviating the volume expansion problem of the lithium-containing particles in the composite negative electrode during the cycle; the surface of the cocoon structure lithium carbon material in the composite negative electrode has micro-nano-sized textures formed by the structural carbon material, which is relatively rough and has certain flexibility and ductility, and has good contact with the negative electrode material, the conductive agent and the binder. Even if the lithium-containing particles form holes or cavities after the action, the cocoon can keep the electronic path unobstructed, adjust the current density to be uniform, effectively solve the problem of lithium dendrite growth due to uneven current density, and has good cycle performance and rate performance. 。
[0009] The design of the weight proportions of the cocoon structure lithium-carbon material and the negative electrode material can not only serve as a pre-lithium agent to improve the initial coulombic efficiency of the negative electrode material, but can also serve as a lithium source to continuously provide lithium ions during the cycle, thereby improving the capacity and cycle performance of the composite negative electrode. If the weight proportion of the cocoon structure lithium-carbon material is too small, it can only serve as a pre-lithium agent and cannot replenish the loss of lithium ions during the cycle; if the weight proportion of the cocoon structure lithium-carbon material is too large, the composite negative electrode will exhibit performance similar to that of a metallic lithium negative electrode, and the cycle life will be significantly reduced. The use of the cocoon structure lithium-carbon material in combination with the negative electrode material can not only overcome the problems existing in the use of a single negative electrode material or a cocoon structure lithium-carbon material, but also reduce the amount of conductive agent and binder in the composite negative electrode.
[0010] In the present invention, there is no specific limitation on the type of current collector, which may be ordinary copper foil, carbon-coated copper foil, composite copper foil, copper mesh, nickel foil, nickel mesh. As long as it is a type commonly used by technicians in this field, it is applicable to the present invention.
[0011] Optionally, the negative electrode active material layer is composed of 44-68 parts of negative electrode material, 30-50 parts of cocoon structure lithium carbon material, 1-3.5 parts of conductive agent, and 1-2.5 parts of binder. The composition by weight fully reflects the advantages of cocoon structure lithium carbon material, which can be used as a pre-lithium agent to improve the first coulomb efficiency of negative electrode materials and improve the capacity and cycle performance of negative electrodes; the lithium-containing particles are sticky and can reduce the amount of binder in the negative electrode. The cocoon body has good conductivity and can reduce the amount of conductive agent in the negative electrode.
[0012] Optionally, the lithium-containing particles include metallic lithium powder and / or lithium alloy powder, preferably lithium alloy powder. The lithium alloy powder will have some residue after functioning, and the residue can guide the deposition of metallic lithium during the cycle and maintain the structural stability of the composite negative electrode.
[0013] Optionally, the lithium alloy powder includes any one of lithium boron alloy, lithium silver alloy, lithium tin alloy, lithium silicon alloy, lithium zinc alloy, lithium indium alloy, lithium aluminum alloy or lithium magnesium alloy, or a combination of at least two of them, preferably any one of lithium boron alloy, lithium indium alloy, lithium silver alloy or lithium magnesium alloy, or a combination of at least two of them.
[0014] Optionally, the average particle size of the lithium-containing particles is 1-100 μm, for example, 1 μm, 3 μm, 5 μm, 7 μm, 10 μm, 15 μm, 20 μm, 30 μm, 40 μm, 45 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm or 100 μm, etc., preferably 10-50 μm. The average particle size of the metallic lithium powder and / or lithium alloy powder can be obtained by testing with a laser particle size analyzer under a protective atmosphere.
[0015] Optionally, the structural carbon material includes micro-nano carbon materials, as long as one dimension is micrometer or nanometer. The micro-nano carbon material includes any one or a combination of at least two of graphene nanosheets, graphene nanoribbons, multi-walled carbon nanotubes, single-walled carbon nanotubes, carbon fibers or few-walled carbon nanotubes, including but not limited to graphene nanosheets and few-walled carbon nanotubes, multi-walled carbon nanotubes and single-walled carbon nanotubes, graphene nanoribbons and carbon fibers, single-walled carbon nanotubes and nickel nanowires, etc., preferably any one or a combination of at least two of graphene nanosheets, single-walled carbon nanotubes or few-walled carbon nanotubes.
[0016] Optionally, the mass ratio of the lithium-containing particles to the structural carbon material is (1-1000):1, for example, it can be 1:1, 5:1, 10:1, 30:1, 50:1, 100:1, 120:1, 150:1, 200:1, 300:1, 400:1, 500:1, 600:1, 700:1, 750:1, 800:1, 850:1, 900:1, 950:1 or 1000:1, etc. If the mass ratio is too small, the micro-nano carbon material is easy to entangle itself, unevenly distributed on the surface of the lithium-containing particles, and the energy density of the composite material will be reduced; if the mass ratio is too large, a stable porous skeleton cannot be formed, preferably (10-500):1.
[0017] Optionally, the lithium-containing particles include metallic lithium powder and lithium alloy powder, and the mass ratio of the metallic lithium powder to the lithium alloy powder is (0.5-50):1, for example, it can be 0.5:1, 0.8:1, 1:1, 1.5:1, 3:1, 5:1, 8:1, 10:1, 15:1, 20:1, 25:1, 30:1, 35:1, 40:1, 45:1 or 50:1, etc. If the mass ratio is too small, the specific capacity of the composite negative electrode is low, which is not conducive to the improvement of energy density; if the mass ratio is too large, the cycle performance of the composite negative electrode is limited, preferably (1-30):1.
[0018] Optionally, the negative electrode material includes any one or a combination of at least two of graphite, tin-based materials, hard carbon, soft carbon, mesophase carbon microbeads, silicon-carbon materials or silicon-oxygen materials.
[0019] Optionally, the conductive agent includes any one of acetylene black, Ketjen black, Cabot black, conductive graphite, Super P, carbon nanotubes, carbon fibers or graphene, or a combination of at least two thereof.
[0020] Optionally, the binder includes any one of polyvinylidene fluoride, polytetrafluoroethylene, polyvinylidene fluoride-hexafluoropropylene copolymer, sodium carboxymethyl cellulose, styrene-butadiene rubber, polystyrene, polyisobutylene, styrene-butadiene-styrene block copolymer or styrene-ethylene-butylene-styrene block copolymer, or a combination of at least two thereof.
[0021] In a second aspect, the present invention provides a method for preparing the composite negative electrode as described in the first aspect, the method comprising the following steps:
[0022] (1) mixing a negative electrode material, a conductive agent and a binder, and then fibrillating the binder to obtain a mixture;
[0023] (2) The mixture in step (1) is mixed with a cocoon-structured lithium-carbon material, and then hot-pressed into a negative electrode active material layer, and the negative electrode active material layer is disposed on at least one side of a current collector to obtain the composite negative electrode.
[0024] In the present invention, a dry process is adopted to mix the cocoon structure lithium-carbon material with the mixture after the binder is fiberized, which can better maintain the morphology of the cocoon structure. The cocoon structure lithium-carbon material is not consumed during the preparation process, and the obtained composite negative electrode has a higher energy density.
[0025] In the present invention, the preparation method of the cocoon structured lithium-carbon material is not specifically limited. As long as the cocoon structured lithium-carbon material is composed of a cocoon body formed by a structural carbon material and one or more lithium-containing particles contained in the cocoon body, it belongs to the protection scope of the present invention.
[0026] For example, the structured carbon material is dispersed in an organic solvent such as n-hexane or p-xylene, and then lithium-containing particles are added and stirred at a speed of more than 5000 rpm and / or spray granulated to obtain a cocoon structured lithium carbon material. The lithium-containing particles include metallic lithium powder and / or lithium alloy powder, which are extremely active in the air. The implementation of the method is carried out in a protective atmosphere, such as argon and / or helium protection.
[0027] Optionally, the equipment for fiberizing the binder in step (1) is not specifically limited, including but not limited to any one of a planetary high-speed dispersion device, an ultrasonic gasification device or an ultra-strong shearing device, or a combination of at least two of them, preferably an ultra-strong shearing device.
[0028] Optionally, the temperature of the binder fiberization in step (1) is 50-150°C, for example, 50°C, 55°C, 60°C, 70°C, 80°C, 90°C, 95°C, 100°C, 105°C, 110°C,
[0029] 120°C, 130°C, 140°C or 150°C, including but not limited to the listed point values, as long as they are within the above numerical range, they all belong to the protection scope of the present invention, preferably 90-110°C.
[0030] Optionally, the mixing equipment in step (2) is not specifically limited, including but not limited to any one of a V-type mixing equipment, a drum mixing equipment or a planetary high-speed dispersing equipment or a combination of at least two, preferably a V-type mixing equipment and / or a drum mixing equipment.
[0031] Optionally, the mixing time in step (2) is 10-60 min, for example, it can be 10 min, 15 min, 20 min, 25 min, 30 min, 40 min, 45 min, 50 min or 60 min, including but not limited to the listed point values. As long as it is within the above numerical range, it belongs to the protection scope of the present invention, preferably 20-45 min.
[0032] Optionally, the mixing speed in step (2) is 2000-5000rpm, for example, it can be 2000rpm, 2500rpm, 3000rpm, 3500rpm, 4000rpm, 4500rpm or 5000rpm, including but not limited to the listed point values. As long as it is within the above numerical range, it belongs to the protection scope of the present invention, preferably 3000-4500rpm.
[0033] Optionally, the temperature of the hot pressing in step (2) is 80-120°C, for example, it can be 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C or 120°C, including but not limited to the listed point values. As long as it is within the above numerical range, it belongs to the protection scope of the present invention, preferably 90-110°C.
[0034] Optionally, the hot pressing pressure in step (2) is 10-50t, for example, it can be 10t, 15t, 20t, 25t, 30t, 35t, 40t, 45t or 50t, etc., preferably 20-40t.
[0035] As a further preferred technical solution of the present invention, the method comprises the following steps:
[0036] (1) mixing a negative electrode material, a conductive agent and a binder according to parts by weight, and then fibrillating the binder at 90-110° C. to obtain a mixture;
[0037] The negative electrode material includes any one or a combination of at least two of graphite, tin-based materials, hard carbon, soft carbon, mesophase carbon microspheres, silicon-carbon materials or silicon-oxygen materials, with a weight of 44-68 parts;
[0038] The conductive agent includes any one of acetylene black, Ketjen black, Cabot black, conductive graphite, Super P, carbon nanotubes, carbon fiber or graphene, or a combination of at least two of them, with a weight of 1-3.5 parts;
[0039] The binder includes any one or a combination of at least two of polyvinylidene fluoride, polytetrafluoroethylene, polyvinylidene fluoride-hexafluoropropylene copolymer, sodium carboxymethyl cellulose, styrene-butadiene rubber, polystyrene, polyisobutylene, styrene-butadiene-styrene block copolymer or styrene-ethylene-butylene-styrene block copolymer, with a weight portion of 1-2.5 parts;
[0040] (2) The mixture in step (1) and the cocoon structure lithium carbon material are mixed at 3000-4500 rpm for 20-45 min, wherein the weight portion of the cocoon structure lithium carbon material is 30-50 parts, and then hot-pressed into a negative electrode active material layer under 90-110° C. and 20-40t, and the negative electrode active material layer is arranged on at least one side of the current collector to obtain the composite negative electrode.
[0041] The third aspect of the present invention provides an energy storage device, wherein the energy storage device comprises the composite negative electrode as described in the first aspect. The energy storage device includes but is not limited to a lithium ion battery and a lithium ion supercapacitor.
[0042] The present invention has at least one of the following beneficial technical effects:
[0043] 1. In the composite negative electrode provided by the present invention, a structural carbon material with good conductivity is constructed on the surface of the cocoon structure lithium carbon material, which improves the utilization rate of the lithium-containing particles and alleviates the problem of their volume expansion; the surface of the cocoon structure lithium carbon material is relatively rough, and has certain flexibility and ductility, and has good contact with the negative electrode material, the conductive agent and the binder, and can adjust the current density, effectively solving the problem of lithium dendrite growth due to uneven current density, so that the composite negative electrode has good cycle performance and rate performance;
[0044] 2. In the composite negative electrode provided by the present invention, the cocoon structure lithium carbon material is uniformly dispersed, which can be used as a lithium supplement to improve the initial coulombic efficiency of the negative electrode, and can also be used as a lithium source to improve the specific capacity of the negative electrode while replenishing the lithium ions continuously consumed during the cycle; the weight of the cocoon structure lithium carbon material and the negative electrode material is reasonably designed, and the amount of the conductive agent and the binder in the composite negative electrode is reduced, which can take into account the specific capacity, cycle performance and rate performance;
[0045] 3. The present invention further improves the cycle performance and rate performance of the composite negative electrode by optimizing the mass ratio of lithium-containing particles to structural carbon materials in the cocoon-structured lithium-carbon material, the weight ratio of each component in the negative electrode active material layer and other parameters;
[0046] 4. The composite negative electrode preparation method provided by the present invention adopts a dry process, and the cocoon structure lithium-carbon material will not be consumed during the preparation process. The structural design of the cocoon structure lithium-carbon material enables good contact between it and the negative electrode material, conductive agent, and binder, thereby improving the specific capacity and structural stability of the composite negative electrode. The preparation method is simple and easy, and is easy to industrialize. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 This is the SEM image of the cocoon structure lithium carbon material in Example 2;
[0048] Figure 2is a cross-sectional SEM image of the composite negative electrode in Example 2;
[0049] Figure 3 This is a cross-sectional SEM image of the composite negative electrode in Comparative Example 1. DETAILED DESCRIPTION
[0050] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0051] Example 1
[0052] The present embodiment provides a composite negative electrode, which includes a copper foil and a negative electrode active material layer arranged on one side of the copper foil, wherein the negative electrode active material layer is composed of 40 parts of graphite, 50 parts of cocoon-structured lithium-carbon material, 5 parts of multi-walled carbon nanotubes, and 5 parts of polytetrafluoroethylene; the cocoon-structured lithium-carbon material includes a cocoon body formed by graphene sheets and metallic lithium powder contained in the cocoon body.
[0053] The preparation method of the composite negative electrode comprises the following steps:
[0054] (1) 60 g of lithium metal powder with an average particle size of 10 μm, 60 g of graphene sheets of structural carbon material and 300 g of n-hexane were dispersed at a high speed of 8000 rpm for 30 min, filtered and dried to obtain a lithium carbon material with a cocoon structure;
[0055] (2) dry-mixing graphite (Bai Te Rui, AGP-7), multi-walled carbon nanotubes and polytetrafluoroethylene according to weight parts, and then performing binder fiberization in an ultra-strong shearing device at a temperature of 50° C. to obtain a mixture;
[0056] (3) The mixture in step (2) and the cocoon structure lithium carbon material are mixed in a V-type mixing device according to weight for 10 minutes at a mixing speed of 5000 rpm, and then hot-pressed at 80° C. and a pressure of 50 t to obtain a negative electrode active material layer, and then the negative electrode active material layer is laminated to the copper foil by pressure composite to obtain the composite negative electrode.
[0057] Example 2
[0058] The present embodiment provides a composite negative electrode, which includes a carbon-coated copper foil and a negative electrode active material layer disposed on both sides of the carbon-coated copper foil, wherein the negative electrode active material layer is composed of 78 parts of silicon carbon, 20 parts of cocoon-structured lithium-carbon material, 1 part of Ketjen black, and 1 part of styrene-butadiene-styrene block copolymer by weight; the cocoon-structured lithium-carbon material includes a cocoon body formed by single-walled carbon nanotubes and a lithium-boron alloy powder contained in the cocoon body, and the boron content in the lithium-boron alloy is 20wt%.
[0059] The preparation method of the composite negative electrode comprises the following steps:
[0060] (1) 60 g of lithium-boron alloy powder with an average particle size of 50 μm, 0.15 g of single-walled carbon nanotubes (purchased from Okoshiel) and 300 g of p-xylene (purchased from Aladdin) were dispersed at a high speed of 12,000 rpm for 15 min, filtered, and dried at 80° C. to obtain a cocoon-structured lithium-carbon material; the cocoon-structured lithium-carbon material was characterized by SEM, and the characterization results are shown as follows: Figure 1 As shown in the figure, it can be clearly seen that the single-walled carbon nanotubes are wrapped around the surface of the lithium-boron alloy powder to form a cocoon structure, which plays a role in binding the lithium-boron alloy powder;
[0061] (2) dry-mixing silicon carbon (Betray, DXB8), Ketjen black and styrene-butadiene-styrene block copolymer by weight, and then performing binder fiberization in an ultra-strong shearing device at a temperature of 100° C. to obtain a mixture;
[0062] (3) The mixture in step (2) and the cocoon structure lithium carbon material were mixed in a V-type mixing device according to weight for 30 minutes at a mixing speed of 4000 rpm, and then hot-pressed at 100°C with a pressure of 30 tons to obtain a negative electrode active material layer, and the negative electrode active material layer was laminated to the carbon-coated copper foil by pressure lamination to obtain the composite negative electrode. The SEM of the test cross section of the composite negative electrode, the test results are as follows Figure 2 As shown, it can be clearly seen from the figure that the components in the composite negative electrode are evenly distributed, and the cocoon-structured lithium-carbon material maintains the cocoon structure and is tightly combined with other components.
[0063] Example 3
[0064] The present embodiment provides a metallic lithium composite negative electrode, the composite negative electrode comprising a copper mesh and negative electrode active material layers arranged on both sides of the copper mesh, the negative electrode active material layers are composed of 55 parts of hard carbon, 40 parts of cocoon structure lithium carbon material, 2.5 parts of Ketjen black, and 2.5 parts of styrene-ethylene-butylene-styrene block copolymer; the cocoon structure lithium carbon material comprises a cocoon body formed by carbon nanofibers and a lithium-indium alloy powder contained in the cocoon body, and the indium content in the lithium-indium alloy is 20wt%.
[0065] The composite negative electrode comprises the following steps:
[0066] (1) 60 g of lithium-indium alloy powder with an average particle size of 100 μm, 0.06 g of carbon nanofibers (purchased from Aladdin) and 450 g of tetrahydrofuran (purchased from Aladdin) were dispersed at a high speed of 8000 rpm for 20 min, and then spray granulated at an air inlet temperature of 220° C., an air outlet temperature of 100° C., and a pressure of 0.5 MPa to obtain a cocoon-structured lithium-carbon material;
[0067] (2) dry-mixing hard carbon (Bai Te Rui, BHC-400), Ketjen black and styrene-butadiene-styrene block copolymer according to weight parts, and then performing binder fiberization in an ultra-strong shearing device at a temperature of 120° C. to obtain a mixture;
[0068] (3) The mixture in step (2) and the cocoon structure lithium carbon material are mixed in a drum mixing device according to weight for 30 minutes at a mixing speed of 4000 rpm, and then hot-pressed at 100° C. and a pressure of 30 t to obtain a negative electrode active material layer, and the negative electrode active material layer is laminated to a copper mesh by pressure composite to obtain the composite negative electrode.
[0069] Example 4
[0070] Compared with Example 2, the mass of the single-walled carbon nanotubes in step (1) was replaced with 65 g, and the other conditions remained unchanged.
[0071] Example 5
[0072] Compared with Example 2, the mass of the single-walled carbon nanotubes in step (1) was replaced with 0.05 g, and the other conditions remained unchanged.
[0073] Example 6
[0074] Compared with Example 2, the weight composition of the negative electrode active material layer is replaced by: 68 parts of silicon carbon, 30 parts of cocoon structure lithium carbon material, 1 part of conductive agent, and 1 part of binder.
[0075] Example 7
[0076] Compared with Example 2, the weight composition of the negative electrode active material layer is replaced by: 44 parts of silicon carbon, 50 parts of cocoon structure lithium carbon material, 3.5 parts of conductive agent, and 2.5 parts of binder.
[0077] Example 8
[0078] Compared with Example 2, the lithium-boron alloy powder is replaced by a mixture of metallic lithium powder and lithium-boron alloy powder, the mass ratio of metallic lithium powder to lithium-boron alloy powder is 1:1, and other conditions remain unchanged.
[0079] Example 9
[0080] Compared with Example 2, the lithium-boron alloy powder is replaced by a mixture of metallic lithium powder and lithium-boron alloy powder, the mass ratio of metallic lithium powder to lithium-boron alloy powder is 30:1, and other conditions remain unchanged.
[0081] Example 10
[0082] Compared with Example 2, the lithium-boron alloy powder is replaced by a mixture of metallic lithium powder and lithium-boron alloy powder, the mass ratio of metallic lithium powder to lithium-boron alloy powder is 60:1, and other conditions remain unchanged.
[0083] Comparative Example 1
[0084] Compared with Example 2, the only difference is that the cocoon structure lithium carbon material in the negative electrode active material layer is replaced with metal lithium powder, and the other conditions remain unchanged. The SEM image of the composite negative electrode test cross section is as follows: Figure 3 As shown in the figure, it can be clearly seen that the gaps between the metal lithium powder and the negative electrode material and the conductive agent are large, and the contact is poor.
[0085] Comparative Example 2
[0086] Compared with Example 2, the only difference is that the cocoon-structured lithium-carbon material in the negative electrode active material layer is replaced by a lithium-boron alloy, the boron content in the lithium-boron alloy is 20 wt %, and the other conditions remain unchanged.
[0087] Comparative Example 3
[0088] Compared with Example 2, the only difference is that the cocoon-structured lithium-carbon material in the negative electrode active material layer is replaced by a mixture of lithium-boron alloy and single-walled carbon nanotubes, in which the single-walled carbon nanotubes and lithium-boron alloy are randomly dispersed without forming a cocoon structure, and the other conditions remain unchanged.
[0089] Comparative Example 4
[0090] Compared with Example 1, the only difference is that the cocoon structure lithium carbon material in the negative electrode active material layer is replaced by a metal lithium-lithiophilic skeleton composite material, and the other conditions remain unchanged;
[0091] The preparation method of the metal lithium-lithiophilic skeleton composite material comprises the following steps:
[0092] (1) Polyvinyl alcohol (Aladdin Reagent (Shanghai) Co., Ltd.), polystyrene microspheres (Suzhou Weimai New Materials Co., Ltd.), carbon nanotubes (Shandong Dazhan, carbon tube model: GTC-304), isothiazolinone (Aladdin Reagent (Shanghai) Co., Ltd.) and deionized water in a mass ratio of 5:7:10:10:500 were uniformly mixed to obtain a slurry with a solid content of 6%;
[0093] (2) The slurry was atomized and granulated by a two-fluid atomizer, the carrier gas pressure was 0.3 MPa, and the atomization chamber temperature was set to 220°C;
[0094] (3) placing the carbon particles obtained by the spray granulation into a crucible and subjecting them to high temperature treatment under the protection of an inert atmosphere at a temperature of 800° C. for 3 hours;
[0095] (4) The carbon particles after high temperature treatment are mixed with molten metal lithium and stirred evenly to obtain a metal lithium lithiophilic skeleton composite material.
[0096] The preparation method of the mixture comprises the following steps:
[0097] 60 g of lithium-boron alloy powder with an average particle size of 50 μm, 0.15 g of single-walled carbon nanotubes (purchased from Okoshiel) and 300 g of p-xylene (purchased from Aladdin) were mechanically stirred at a speed of 1000 rpm for 15 min, filtered, and dried at 80°C to obtain a mixture of lithium-boron alloy and single-walled carbon nanotubes.
[0098] Material performance testing:
[0099] The negative electrodes provided in Examples 1-10 and Comparative Examples 1-4 were assembled with lithium sheets to test specific capacity, and assembled with NCM811 to test cycle performance and rate performance. The test results are shown in Table 1.
[0100] Table 1
[0101]
[0102] From Table 1, we can see the following points:
[0103] (1) By comparing Example 2 and Examples 4-5, it can be seen that the structural carbon material used in Example 4 is more than that in Example 2, and the negative electrode specific capacity is lower; the structural carbon material used in Example 5 is less than that in Example 2. Although the specific capacity of the negative electrode is higher, the cycle performance and rate performance are worse than those of Example 2;
[0104] (2) By comparing Example 2 with Examples 6-7, it can be seen that by adjusting the proportion of the cocoon structure lithium-carbon material in the negative electrode, the specific capacity, cycle performance and rate performance of the composite negative electrode in Examples 6 and 7 are better than those in Example 2. That is, the weight composition of the negative electrode material layer in the composite negative electrode in Examples 6 and 7 is better than that in Example 2, and the specific capacity, cycle performance and rate performance of the composite negative electrode can be taken into account;
[0105] (3) By comparing Example 2 with Examples 8-10, it can be seen that the lithium-containing particles used in Examples 8-10 are a mixture of lithium-boron alloy powder and metallic lithium powder. The specific capacity, cycle performance and rate performance of the composite negative electrode of Examples 8 and 9 are better than those of Example 2. This is because the ratio of metallic lithium powder to lithium-boron alloy powder is controlled within a suitable range. Although the specific capacity of the composite negative electrode of Example 10 is higher than that of Example 2, its cycle performance and rate performance are worse than those of Example 2. This is because the ratio of metallic lithium powder in the lithium-containing particles in Example 10 is higher.
[0106] (4) By comparing Example 2 with Comparative Examples 1-3, it can be seen that the specific capacity of the composite negative electrode in Example 2 is lower than that in Comparative Example 1, but the cycle performance and rate performance are better than those in Comparative Example 1. This is because the cocoon-structured lithium-carbon material in Example 2 contains a lithium-boron alloy, which can serve as a skeleton to stabilize the composite negative electrode structure and guide the deposition of metallic lithium, making it difficult to form lithium dendrites. The structural carbon material also alleviates the volume expansion of the lithium-boron alloy and regulates the conductivity of the composite negative electrode. The metallic lithium powder in Comparative Example 1 is prone to form holes after taking effect, causing the electronic path to be disconnected. The performance of the composite negative electrode in Comparative Examples 2 and 3 is worse than that in Example 2, because the cocoon structure is not constructed on the surface of the lithium-boron alloy in the composite negative electrode of Comparative Examples 2 and 3.
[0107] (5) By comparing Example 1 and Comparative Example 4, it can be seen that the specific capacity, cycle performance and rate performance of the composite negative electrode in Example 1 are all better than those in Comparative Example 4. This is because the content of metallic lithium in the metallic lithium-lithiophilic skeleton material in Comparative Example 4 is relatively small (limited by the preparation method, molten metallic lithium is easily coated on the surface of porous particles), and the specific capacity of the composite negative electrode is lower than that in Example 1; the lithium-philic skeleton is inside the metallic lithium, and its role in supporting and regulating the current density of the metallic lithium is more than that in binding it, and it has good contact with the negative electrode material and the conductive agent, while the structural carbon material of the cocoon-structured lithium-carbon material in the present invention binds the lithium-containing particles, effectively alleviating the problem of volume expansion of the lithium-containing particles; the cocoon-structured lithium-carbon material has good contact with the negative electrode material and the conductive agent, and the composite negative electrode has good structural stability.
[0108] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs can make appropriate changes and modifications to the above embodiments. Therefore, the present invention is not limited to the specific embodiments disclosed and described above, and some modifications and changes to the present invention should also fall within the scope of protection of the claims of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.
Claims
1. A composite negative electrode, characterized in that: The composite negative electrode comprises a current collector and a negative electrode active material layer disposed on at least one side of the current collector, wherein the negative electrode active material layer is composed of: The sum of the weight parts of all components in the negative electrode active material layer is 100 weight parts, The cocoon-structured lithium-carbon material comprises a cocoon body formed of a structural carbon material and one or more lithium-containing particles contained in the cocoon body.
2. The composite negative electrode according to claim 1, characterized in that The negative electrode active material layer is composed of:
3. The composite negative electrode according to claim 1, characterized in that The lithium-containing particles include metallic lithium powder and / or lithium alloy powder; The lithium alloy powder includes any one or a combination of at least two of lithium boron alloy, lithium silver alloy, lithium tin alloy, lithium silicon alloy, lithium zinc alloy, lithium indium alloy, lithium aluminum alloy or lithium magnesium alloy; Wherein, the average particle size of the lithium-containing particles is 1-100 μm.
4. The composite negative electrode according to claim 1, characterized in that: The structural carbon material includes micro-nano carbon material, and the micro-nano carbon material includes any one of graphene nanosheets, graphene nanoribbons, multi-walled carbon nanotubes, single-walled carbon nanotubes, carbon fibers or few-walled carbon nanotubes, or a combination of at least two thereof.
5. The composite negative electrode according to claim 1, characterized in that: The mass ratio of the lithium-containing particles to the structural carbon material is (1-1000):1; When the lithium-containing particles include metallic lithium powder and lithium alloy powder, the mass ratio of the metallic lithium powder to the lithium alloy powder is (0.5-50):
1.
6. The composite negative electrode according to claim 1, characterized in that: The negative electrode material includes any one or a combination of at least two of graphite, tin-based materials, hard carbon, soft carbon, mesophase carbon microspheres, silicon-carbon materials or silicon-oxygen materials; The conductive agent includes any one or a combination of at least two of acetylene black, Ketjen black, Cabot black, conductive graphite, Super P, carbon nanotubes, carbon fibers or graphene; The binder includes any one of polyvinylidene fluoride, polytetrafluoroethylene, polyvinylidene fluoride-hexafluoropropylene copolymer, sodium carboxymethyl cellulose, styrene-butadiene rubber, polystyrene, polyisobutylene, styrene-butadiene-styrene block copolymer or styrene-ethylene-butylene-styrene block copolymer, or a combination of at least two thereof.
7. A method for preparing a composite negative electrode as claimed in any one of claims 1 to 6, characterized in that: The method comprises the following steps: (1) mixing a negative electrode material, a conductive agent and a binder, and then fibrillating the binder to obtain a mixture; (2) The mixture in step (1) is mixed with a cocoon-structured lithium-carbon material, and then hot-pressed into a negative electrode active material layer, and the negative electrode active material layer is disposed on at least one side of a current collector to obtain the composite negative electrode.
8. The method according to claim 7, characterized in that The temperature of the binder fiberization in step (1) is 50-150°C.
9. The method according to claim 7, characterized in that: The mixing time in step (2) is 10-60 min, and the mixing speed is 2000-5000 rpm; The temperature of the hot pressing in step (2) is 80-120° C. The hot pressing pressure in step (2) is 10-50t.
10. An energy storage device, characterized in that: The energy storage device comprises the composite negative electrode according to any one of claims 1 to 6.
Citation Information
Patent Citations
High-capacity metal lithium powder composite cathode and preparation method thereof, and multi-layer composite electrode
CN102201565A